2016
DOI: 10.1152/ajplung.00135.2016
|View full text |Cite
|
Sign up to set email alerts
|

Susceptibility for cigarette smoke-induced DAMP release and DAMP-induced inflammation in COPD

Abstract: Cigarette smoke (CS) exposure is a major risk factor for chronic obstructive pulmonary disease (COPD). We investigated whether CS-induced damage-associated molecular pattern (DAMP) release or DAMP-mediated inflammation contributes to susceptibility for COPD. Samples, including bronchial brushings, were collected from young and old individuals, susceptible and nonsusceptible for the development of COPD, before and after smoking, and used for gene profiling and airway epithelial cell (AEC) culture. AECs were exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
67
1

Year Published

2018
2018
2020
2020

Publication Types

Select...
4
2
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 67 publications
(76 citation statements)
references
References 26 publications
6
67
1
Order By: Relevance
“…One underlying biological mechanism that may provide insight into COPD pathogenesis and progression is mitochondrial dysfunction, which is consistently observed in cells derived from COPD subjects (5)(6)(7)(8)(9)(10)(11)(12)(13), as well as in experimental COPD models (11,14). Such mitochondrial dysfunction is associated with the leakage of mitochondrial DNA (mtDNA) (15)(16)(17)(18)(19), a mitochondrial derived danger-associated molecular pattern (mtDAMP) (20,21). Intracellularly, mtDNA acts as an essential second messenger that activates pathogen recognition receptors (PRRs) -in particular, the NLRP3 inflammasome and the DNA sensor cyclic GMP-AMP synthase (cGAS), eliciting a series of innate immune signaling cascades (21)(22)(23)(24).…”
Section: Introductionmentioning
confidence: 99%
“…One underlying biological mechanism that may provide insight into COPD pathogenesis and progression is mitochondrial dysfunction, which is consistently observed in cells derived from COPD subjects (5)(6)(7)(8)(9)(10)(11)(12)(13), as well as in experimental COPD models (11,14). Such mitochondrial dysfunction is associated with the leakage of mitochondrial DNA (mtDNA) (15)(16)(17)(18)(19), a mitochondrial derived danger-associated molecular pattern (mtDAMP) (20,21). Intracellularly, mtDNA acts as an essential second messenger that activates pathogen recognition receptors (PRRs) -in particular, the NLRP3 inflammasome and the DNA sensor cyclic GMP-AMP synthase (cGAS), eliciting a series of innate immune signaling cascades (21)(22)(23)(24).…”
Section: Introductionmentioning
confidence: 99%
“…Understanding genetics is also key to unraveling the causes and potential future treatments for many lung diseases. Those patients with both genetic and environmental determinants, such as in those who smoke and have genes associated with COPD, are at the greatest risk [228].…”
Section: Resultsmentioning
confidence: 99%
“…Significance between the scrambled control and the siRNA-treated cells over the range of concentrations was tested using a two-way ANOVA with Bonferroni correction, # p < 0.05. cigarette smoke-induced airway inflammation in mice 19 . Moreover, this DAMP is specifically released upon cell death and a reliable marker for CSE-induced DAMP release from primary bronchial epithelial cells 8 . In the current study we observed an increase in dsDNA and RNA release in CFLAR deficient cells upon CSE exposure.…”
Section: Discussionmentioning
confidence: 99%
“…Cells were grown to confluence and serum-deprived overnight before use. Cigarette smoke extract (CSE) was prepared as described before with two filterless Kentucky 3R4F research-reference SCIENTIfIC REPORtS | (2018) 8:12426 | DOI:10.1038/s41598-018-30602-7 cigarettes and a Watson Marlow 603S smoking pump at a rate of 8 L/hr (Watson-Marlow, Delden, The Netherlands) 5,8 . The 100% CSE mixture was prepared by bubbling the CS of two cigarettes through 25 mL of RPMI-1640 medium supplemented with 100 U/ml penicillin and 100 mg/mL streptomycin.…”
Section: Cflar Gene Expression Analysismentioning
confidence: 99%